Estimated Glomerular Filtration Rates Calculated by New and Old Equations in Children and Adolescents With Type 1 Diabetes—What to Do With the Results? - Boettcher, Claudia; Utsch, Boris; Galler, Angela; Grasemann, Corinna; Borkenstein, Martin; Denzer, Christian; Heidtmann, Bettina; Tittel, Sascha R.; Holl, Reinhard W.; , DPV initiative (Frontiers in Endocrinology, 2020)
Background: To apply and evaluate various equations for estimated glomerular filtration rates (eGFR) in a large paediatric type 1 diabetes population and compare the eGFR values with urinary creatinine clearances (UCC) in a subset of patients. Methods: Six eGFR formulae applicable for children and adolescents were used for calculation of eGFR values in 36,782 children/adolescents with type 1 diabetes. Via regression models, factors influencing eGFR values were identified. eGFR values were compared with measured urinary UCC in 549 patients. Spearman correlation coefficients were given to assess the relation of eGFR and UCC values. Bland-Altman-Plots with corresponding linear regression were drawn to evaluate the agreement between eGFR and UCC. Results: eGFR values differed widely depending on the formula used, resulting in a percentage of pathological values < 60 mL/min/1.73m2 up to 8%. Regression models showed age, sex and duration of diabetes as influencing factors. Microalbuminuria was associated with significantly higher eGFR values for all formulae. In comparison of eGFR with UCC, the highest correlation coefficient was 0.33, the lowest 0.01. Bland-Altman-Plots demonstrated graphically a poor agreement between eGFR and UCC, regardless of the formula used. Conclusions: The broad range of eGFR values indicate that an ideal eGFR formula for children and adolescence with T1D is yet missing. The minimal agreement between measured UCC and eGFR values urges us to be careful in application and interpretation of eGFR values regardless of the formula used.